Role of Microfinance in Poverty Alleviation: Evidence from Pakistan - Awan, Abdul Ghafoor; Juiya, Muhammad Javed Iqbal (American Journal of Trade and Policy, 2015)
This study has empirically measured the role of microfinance in poverty alleviation and has examined its impact on household poverty level. The factors that can affect the household poverty and living standard have been investigated with innovative econometric technique that is binary logit model and ordered logit model by using Stata software. The empirical analysis of this study is based on fresh data. The data is collected through a household survey method from the rural and urban areas of district Lodhran of Pakistan. A questionnaire was developed to collect primary data which covered the household loan amount, household assets, and household expenditures. The questionnaires were distributed among 220 respondents. We selected total 19 variables: eleven variables to analyze the factors responsible for household poverty and eight variables to measure the household living standard. High value of Living standard shows high living standard and low value shows lower living standard. The empirical evidence shows that the variables such as gender, married status, chronicle diseases, purpose of loans, number of loans taken, amount of loan, Lives Stock, Monthly savings, total number of household members are found impacting poverty significantly while the impact of transport facility, years of schooling and ownership of land were found insignificant. While measuring poverty level we followed World Bank poverty line which is $ 1.25 (Rs.3750) per capita per adult monthly income and expenditure. The data shows that 137 (62.3 percent) households are living below poverty line while 83 households are living above poverty line. We find that 169 households (76.8 percent of the total sample) have good living standard while 20 households (9.1 percent) have high living standard whereas 31 households (14.1 percent), have very low living standard.JEL Classifications Code: E6
Keywords: microfinance; availability of loan; gender; monthly saving; marital status; poverty; alleviation